Fox and furious : a novel [large type] - Brown, Rita Mae (Brown, Rita Mae. Sister Jane series, 2026)
A mystery novel set in rural Virginia featuring "Sister" Jane Arnold. During hunting season, two brothers become embroiled in a dispute over their late mother's estate, including acreage and a hunting kennel. After a violent argument, one brother is found dead and suspicion falls on the other. Doubting the apparent motive, Sister Jane undertakes her own investigation, assisted by her close-knit hunting community. The novel explores themes of family conflict, inheritance, and small-town relationships within the framework of a traditional murder mystery.